Monitoring And Notification Tools on Portable Incubator with Microcontroller and Short Message Service (SMS) - Irmansyah, M.; Efrizon, Efrizon; Madona, Era; N, Anggara (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2021)
Portable incubator was one solution to help premature baby. In general, the baby in the incubator monitored by observer manually. The aim of this research was applied a microcontroller, temperature sensor, weight sensor, heart rate sensor and GSM module to monitor and give notification the premature babies condition in portable incubators. The observation can be done by read the display on LCD and SMS. The hardware used consists of a DS18B20 sensor, Load Cell, Pulse Heart Rate Sensor, Buzzer, LCD and SIM800L Module. The results showed that the Pulse sensor and DS18B20 sensor can measure and detect the baby's heart rate, body temperature and are displayed on the LCD with an average error of 4.354% and 1.437%. The loadcell sensor can detect weight with an error of 2.16%. The duration of sending SMS to Smartphone is 8s for each delivery. SMS was sent if the patient conditions weak and critical. This monitoring and notification tools hopefully can inform the condition of the baby in the incubator immediately.